1987
DOI: 10.1177/002076408703300302
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia in Rural Ireland: a Case of Service Overutilisation

Abstract: Rural Ireland has been characterised by various studies as having high rural rates of schizophrenia. This paper tested the hypothesis that these anomalously high rates resulted from overutilisation of psychiatric hospitals, reflecting community differences in risk for readmission. A comparison of first and total admission (1978-1981), in two broadly matched rural counties showed no significant difference in treated incidence but significant differences in treated prevalence. A demographic comparison of admitta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Paradoxically, the highest prevalence ever measured (17.4 per 1000 population) was reported from a thinly populated rural area of County Roscommon in the West of Ireland (Torrey, 1987), though there seems to be no evidence that this represented a higher-than-average incidence rate. What these anomalous rural areas may have as a common factor is a high proportion of unmarried males, living as farmers or rural labourers (Keatinge, 1987). Thornicroft et al (1993) found that a rural area of the Veneto had twice the treated incidence and prevalence of urban South Verona, but offered no explanation for this.…”
mentioning
confidence: 99%
“…Paradoxically, the highest prevalence ever measured (17.4 per 1000 population) was reported from a thinly populated rural area of County Roscommon in the West of Ireland (Torrey, 1987), though there seems to be no evidence that this represented a higher-than-average incidence rate. What these anomalous rural areas may have as a common factor is a high proportion of unmarried males, living as farmers or rural labourers (Keatinge, 1987). Thornicroft et al (1993) found that a rural area of the Veneto had twice the treated incidence and prevalence of urban South Verona, but offered no explanation for this.…”
mentioning
confidence: 99%
“…After removing duplicate records, our initial search identified 1,975 citations (Fig. 1) of which 21 met our inclusion criteria (Scully et al, 2002;Nkire et al, 2021;O'Donoghue et al, 2016;Keatinge 1986;Baldwin et al, 2005;Morgan et al, 2001;Omer et al, 2012;Keatinge 1987;Daly et al, 1995;Baldwin et al, 2002;Waddington et al, 2004;Kingston et al, 2011;Baldwin et al, 2003;Owoeye et al, 2013;Lyne et al, 2014;Keatinge 1988;Ninuallain et al, 1987;Kelly et al, 2010;Jablensky et al, 1992;Omer et al, 2014). Via author contacting, we identified a further two citations which met inclusion criteria (O'Donoghue et al, 2021;Fayyaz et al, 2021).…”
Section: Study Selectionmentioning
confidence: 99%
“…Six citations provided incidence data from studies partially set in Dublin (O'Donoghue et al, 2021;O'Donoghue et al, 2016;Daly et al, 1995;Lyne et al, 2014;Kelly et al, 2010;Jablensky et al, 1992), including the World Health Organization [WHO] Ten-country study (Jablensky et al, 1992) and three citations from the DETECT EIP service (O'Donoghue et al, 2021;O'Donoghue et al, 2016;Lyne et al, 2014). Other locations included Clare and Wexford (O'Donoghue et al, 2016;Keatinge 1986;Keatinge 1987;Lyne et al, 2014), Waterford (Keatinge 1988) andCarlow, Westmeath andRoscommon (Ninuallain et al, 1987), as part of the 'The Three-County Study'.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The precise relevance of rural dwelling was further explored in the 1980s when a study of admissions in one rural and one urban area (between 1978 and 1980) showed that readmission rates for schizophrenia were equivalent in urban and rural areas, but that people with schizophrenia in rural areas were admitted at a later age (Keatinge, 1988). Furthermore, while incidence rates did not differ between rural counties, treated prevalence and readmission rates did, indicating that social and community variables significantly influenced psychiatric hospital utilisation (Keatinge, 1987a(Keatinge, , 1987b. As was becoming apparent, the idea of a higher rate of incidence of mental disorder among the Irish was inseparable from the higher rate of hospitalisation, and it was not entirely clear that the two could be meaningfully separated, using available data.…”
mentioning
confidence: 99%